PENGARUH RASIO DAGING DAN KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP KARAKTERISTIK SELAI - Hardita, Anindya Putri; Yusa, Ni Made; Djuniaji, Agus Slamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 1 (2016): Jurnal ITEPA, 2016)
The aim of this research was to know effect the ratio of pulp and peel of a dragon fruit to the characteristic of jam, and determine the best the ratio made by those pulp and peel, in order to able to produce a good characteristic of jam. This research used Complete Random Design with the treatment comparison of pulp and peel of dragon fruit comprised of 5 (five) treatments, such as 90% pulp : 10% peel, 70% pulp : 30% peel, 50% pulp : 50% peel, 30% pulp : 70% peel, 10% pulp : 90% peel. All of treatments were repeated for 3 times to obtain 15 research units. Data were analyzed using analysis of variance and if an influences occurred among the treatments, the research would be continued to the Duncan’s test. Results of this research had showed that the comparison ratio of pulp and peel of dragon fruits gave influences to the water content, total sugar, total soluble solid, viscosity, pH balance, antioxidant capacity, color, flavor, texture and overall acceptance of a jam. The best ratio of pulp and peel of dragon fruits showed of percentage 30% pulp : 70% peel with 33,42% water content, 31,85% total sugar, 64,80%brix total soluble solids, 0,015% antioxidant capacity, viscosity  0,053 cm/second, 3,99 pH, aroma (normal), color, flavor, texture and overall acceptance (like).
Keywords: pulp and peel of dragon fruits, characteristic, jam.